Diagnostic accuracy of hemoglobin-a1c compared to fasting plasma glucose for early detection of diabetes mellitus: A systematic review - Surbakti, Dawina Yohanna (Holistik Jurnal Kesehatan, 2025)
Background: Diabetes mellitus (DM) is a global health problem with rising prevalence, including in Indonesia. Diagnosis traditionally relies on fasting plasma glucose (FPG) or oral glucose tolerance test (OGTT), but both have technical limitations. Hemoglobin A1c (HbA1c) has emerged as an alternative, reflecting average glucose levels over the previous 2–3 months. Purpose: To review the comparative diagnostic accuracy of HbA1c versus FPG in early detection of DM. Method: Systematic literature review research using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method and the PICOS approach, namely P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome) and S (study). Writing literature with keywords “HbA1c” OR “Fasting Plasma Glucose”, AND “Diabetes Mellitus”. From the 159 articles identified, screening was conducted according to the topic of discussion, resulting in 5 articles related to the comparison of the diagnostic accuracy of HbA1c with FPG in the early detection of DM. Results: Five primary studies involving 54,746 participants from Asia and the United States met inclusion criteria. Most applied HbA1c cut-offs ≥6.5% and FPG ≥7.0 mmol/L. Findings showed HbA1c had higher sensitivity (up to 82.5% in Singapore), whereas FPG demonstrated greater specificity (up to 96.9%) with superior positive predictive value. Area under the curve (AUC) ranged from 0.73–0.93; HbA1c performed better in community-based populations, while FPG was more accurate in high-risk clinical populations. Heterogeneity was influenced by cut-off variation, population characteristics, comorbidities, age, BMI, and reference standards. Conclusion: HbA1c is more practical and sensitive for large-scale community screening, while FPG remains highly specific and appropriate for diagnostic confirmation. Selection of diagnostic method should consider clinical context, population characteristics, and local resource availability.   Keywords: Diabetes Mellitus; Early Detection; Fasting Plasma Glucose; Hemoglobin A1c.   Pendahuluan: Diabetes melitus (DM) merupakan masalah kesehatan global dengan prevalensi meningkat, termasuk di Indonesia. Diagnosis DM umumnya mengandalkan glukosa plasma puasa (FPG) atau uji toleransi glukosa oral (OGTT), namun keduanya memiliki keterbatasan teknis. Pemeriksaan hemoglobin A1c (HbA1c) menjadi alternatif karena merefleksikan kadar glukosa rata-rata 2–3 bulan terakhir. Penelitian ini bertujuan meninjau perbandingan akurasi diagnostik HbA1c dengan FPG dalam deteksi dini DM. Tujuan: Untuk mengevaluasi akurasi diagnostik komparatif antara HbA1c dan FPG dalam deteksi dini diabetes mellitus (DM). Metode: Penelitian literature review menggunakan metode Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Desain pencarian artikel dengan merumuskan PICOS yaitu P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome) dan S (study). Pencarian literatur yang digunakan berasal dari beberapa database, antara lain PubMed, Scopus, Embase, dan Cochrane Library dengan kata kunci “HbA1c” OR “Fasting Plasma Glucose”, AND “Diabetes Mellitus”. Mengidentifikasi 159 artikel selanjutnya dilakukan penyaringan sesuai dengan topik bahasan mendapatkan 5 artikel yang terkait perbandingan akurasi diagnostik HbA1c dengan FPG dalam deteksi dini DM. Hasil: 5 studi primer dari Asia dan Amerika memenuhi kriteria. Sebagian besar menggunakan cut-off HbA1c ≥6.5% dan FPG ≥7.0 mmol/L. Hasil menunjukkan HbA1c memiliki sensitivitas lebih tinggi (hingga 82.5% di Singapura), sedangkan FPG lebih spesifik (hingga 96.9%) dengan nilai prediktif positif lebih baik. Area under the curve (AUC) bervariasi 0.73–0.93; HbA1c lebih unggul pada populasi komunitas, sedangkan FPG lebih akurat pada populasi klinis berisiko tinggi. Variasi cut-off, populasi, komorbid, usia, BMI, dan standar referensi memengaruhi heterogenitas hasil. Simpulan: HbA1c lebih praktis dan sensitif untuk skrining populasi luas, sementara FPG tetap lebih spesifik dan sesuai untuk konfirmasi diagnosis. Pemilihan metode perlu disesuaikan dengan konteks klinis, karakteristik populasi, dan sumber daya lokal.   Kata Kunci: Diabetes Mellitus; Deteksi Dini; Fasting Plasma Glucose; Hemoglobin A1c.